2020
DOI: 10.1007/s00464-020-07368-z
|View full text |Cite
|
Sign up to set email alerts
|

Lesion size and circumferential range identified as independent risk factors for esophageal stricture after endoscopic submucosal dissection

Abstract: Background and aim Endoscopic submucosal dissection (ESD) is used to treat early esophageal cancer and precancerous lesions. Patients undergoing ESD are prone to esophageal stenosis, which impairs therapeutic efficacy and quality of life. This retrospective study aimed to investigate the potential association between patient demographics and esophageal lesion characteristics with the risk of esophageal stenosis following ESD. Methods For this retrospective study 190 consecutive patients who underwent ESD betwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 31 publications
2
20
0
Order By: Relevance
“…Evidence of this study showed that more than 3/4 circumferential esophageal lumen, lesions near upper esophagus, postoperative fever and operation time were the independent risk factors of esophageal stricture after ESD. >3/4 luminal circumference was consistent with the vast majority of previous studies, while the conclusion of other three risk factor varied from literature to literature [7,13].…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Evidence of this study showed that more than 3/4 circumferential esophageal lumen, lesions near upper esophagus, postoperative fever and operation time were the independent risk factors of esophageal stricture after ESD. >3/4 luminal circumference was consistent with the vast majority of previous studies, while the conclusion of other three risk factor varied from literature to literature [7,13].…”
Section: Discussionsupporting
confidence: 89%
“…Multivariate logistic analysis revealed that more than 3/4 of the circumferential extension is a reliable risk factor [4]. But little consensus has been achieved in longitudinal resection length >50mm, the depth of in ltration more than lamina propria (m2), muscular injury and clip number and so on [5][6][7]. Postoperative symptoms and laboratory tests were seldom incorporated into models.…”
Section: Introductionmentioning
confidence: 99%
“…The reported incidence of esophageal post-ESD stenosis is 7.1%–26.8%. [ 10 , 11 , 12 , 13 ] Symptomatic esophageal stenosis and repeated endoscopic dilatation impair patients’ quality of life and predispose them to psychiatric problems, including mood disorder and suicidality. [ 14 ]…”
Section: Introductionmentioning
confidence: 99%
“…Endoscopic submucosal dissection (ESD) sets a standard for precancerous lesions, and early esophageal cancers (ECs) confined to the submucosa with a low risk of distant metastases (1,2).…”
Section: Introductionmentioning
confidence: 99%